Research note. The link between shoplifting and burglary. The booster burglar - Schneider, Jacqueline L. (The British journal of criminology, 2005)
This research note forms part of a larger set of findings from a study that examined disposal patterns of stolen goods. Literature linking shop theft and burglary, as part of an overall criminal career, has been lacking. Results regarding the role that shop theft plays in the criminal careers of prolific, persistent burglars are presented. This article shows that shop theft plays an instrumental role in offending patterns of prolific burglars, thus challenging the notion that shoplifting is a less serious crime than burglary. Given the findings presented here, an argument is made that by detecting more shop thefts, crime-reduction initiatives might also increase their detections for burglary